# Using matrix method, solve the system of equations 3x + 2y – 2z = 3, x + 2y + 3z = 6, 2x – y + z = 2

Given system of equations is:

3x + 2y – 2z = 3,

x + 2y + 3z = 6,

2x – y + z = 2

We know that,

AX = B

i.e. X = A-1 B

So, firstly, we have to find the A-1 and Firstly, we find |A|

Expanding |A| along C1, we get  = 3(2 + 3) – 1(2 – 2) + 2(6 + 4)

= 3(5) + 2(10)

= 15 + 20

= 35

Now, we have to find adj A and for that we have to find co-factors:           Now, X = A-1B    x = 1, y = 1 and z = 1

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos  Determinants of Matrices of different order59 mins  Determining a determinant63 mins  Types of Matrices & Properties51 mins  Interactive Quiz on Matrices and Determinants41 mins  Lecture on Product of Determinants58 mins  Interactive Quiz on Properties of Determinants43 mins  Triangular Matrices & operations on matrices58 mins  Know About finding the Adjoint & Inverse Of Matrix46 mins  Test Yourself, Properties of Determinants30 mins  Interactive Quiz on Matrices & Determinants48 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses 